New treatments for desmoid tumors - Kasper, Bernd (Current opinion in oncology, 2023)
Purpose of review - Desmoid tumor is a rare disease of intermediate malignancy characterized by a locally aggressive monoclonal, fibroblastic proliferation and accompanied by a variable and often unpredictable clinical course. The purpose of this review is to give an overview on the emerging new systemic treatment options for this intriguing disease for which no established or approved drugs are available yet. - Recent findings - Over decades, surgical resection has been the established initial treatment approach; however, more recently, a paradigm shift has been introduced towards a more conservative treatment strategy. Almost 10 years ago, The Desmoid Tumor Working Group has initiated a consensus process initially in Europe and then globally with the intention to harmonize the therapeutic strategy amongst clinicians and set up management recommendations for desmoid tumor patients. - Summary - This review will summarize and focus on the latest emerging impressive data on the use of gamma secretase inhibitors in this disease paving a possible future perspective in the treatment armamentarium for desmoid tumor patients.
Gesehen am 08.08.2023